2016
DOI: 10.1111/cns.12537
|View full text |Cite
|
Sign up to set email alerts
|

Daphnetin Alleviates Experimental Autoimmune Encephalomyelitis via Regulating Dendritic Cell Activity

Abstract: Our findings for the first time demonstrate the property of daphnetin in regulating DCs' function and subsequently Th development. Given the low or absent toxicity associated with daphnetin, our data may suggest a novel safe and effective approach to control autoimmune neuroinflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Daphnetin (DAPH; 7, 8-dihydroxycoumarin) is a coumarin derivative extracted from Daphne odora var. marginata, known to have robust anti-inflammatory and antioxidative properties that is widely used in treating inflammatory diseases (21)(22)(23). Our previous study showed that DAPH alleviated experimental autoimmune encephalomyelitis by regulating dendritic cell activity (22).…”
mentioning
confidence: 99%
“…Daphnetin (DAPH; 7, 8-dihydroxycoumarin) is a coumarin derivative extracted from Daphne odora var. marginata, known to have robust anti-inflammatory and antioxidative properties that is widely used in treating inflammatory diseases (21)(22)(23). Our previous study showed that DAPH alleviated experimental autoimmune encephalomyelitis by regulating dendritic cell activity (22).…”
mentioning
confidence: 99%
“…In addition, 10 mg/kg and 20 mg/kg of DAP protected against cerebral I/R injury to the same degree in this model ( P > 0.05). Based on these results and the previous study [14, 15], the optimal treatment dose of DAP (10 mg/kg) was used in the following experiment.…”
Section: Resultsmentioning
confidence: 97%
“…10 mg/kg and 20 mg/kg of DAP protected against cerebral I/R injury to the same degree, whereas 5 mg/kg of DAP did not show neuroprotective effects. According to this result and the previous study [14, 15], 10 mg/kg was chosen as the optimal treatment dose in the subsequent experiment.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Subsequently, DAP was found to prevent and treat numerous diseases, including cerebral ischaemia/reperfusion injury, rheumatoid arthritis, colitis and endotoxin-induced lung injury, due to its powerful anti-inflammatory activities (24,(27)(28)(29)(30)(31)(32). At present, DAP is an anti-inflammatory agent used in some inflammation-related diseases (33)(34)(35). Li et al (33) reported that DAP inhibited inflammation in the systemic lupus erythematosus murine model via inhibition of NF-κB activity.…”
Section: Introductionmentioning
confidence: 99%